Ecosystem Vulnerability and Sustainable Development Challenges in Libyan Rangelands Under the Influence of Drought Cycles and Climate Change: A Case Study from the Dafna Plateau (Northeastern Libya) - شيماء عبد القادر صالح; نفيسه محمد حسين; منعم وافي براني (African Journal of Advanced Pure and Applied Sciences, 2025)
Climate factors are dynamic phenomena with a significant impact on the environment and sustainable development, especially in semi-arid and arid regions. This research aims to study the effect of the local climate on the characteristics of vegetation cover on the Dofna Plateau (northeast Libya) and the potential for rehabilitating the area and sustainably utilizing its rangelands. The plateau is one of Libya’s important pastoral areas, with a predominantly arid climate (Aridity Index = 0.13), with aridity increasing further south. The average annual rainfall in Tobruk is 184 mm, decreasing to 89 mm in Al-Adam, located about 25 km south. The average annual temperature ranges between 19.1°C and 19.7°C. The arid conditions clearly reflect the fragility of the region's ecosystems. The results showed weak natural characteristics of the vegetation cover, with an average plant cover of 17.4%, while the average distance of bare areas was 1.5 meters, and the average species richness was low (Species Richness = 3). The region is dominated by stunted, poorly palatable, xerophytic plants such as Haloxylon scoparium, Thymelaea hirsuta, Deverra tortuosa, and Suaeda vermiculata. Aridity is expected to intensify under current climate changes, manifested in rising temperatures, decreasing rainfall, and longer dry periods. These challenges, compounded by unsustainable human activities, may also apply to rangeland areas throughout Libya. This necessitates effective human intervention to curb environmental degradation and rehabilitate local ecosystems in light of current data and future climate change projections.